Effect of recent minor volcanic eruptions on temperatures in the upper troposphere and lower stratosphere. (July 2015) - Mehta, Sanjay Kumar; Fujiwara, Masatomo; Tsuda, Toshitaka; Vernier, Jean-Paul
Abstract: The impact of the recent minor volcanic eruptions during 2001–2010 in the temperature of the upper troposphere and lower stratosphere (UTLS) is investigated using data from the Global Positioning System Radio Occultation (GPS RO), three radiosonde compilations and two reanalyses (ERA-Interim and MERRA). The volcanic signals are identified in the residual temperature time series after removal of the linear trend, the quasi-biennial oscillation and El Nino Southern Oscillation components. Eight minor volcanic eruptions (six from the tropics and two from midlatitude) over the last decade (2001–2010) are analyzed in this study. We found significant volcanic signals in the UTLS temperature only in association with the tropical Soufrière Hills and Tavurvur eruptions (in May 2006 and in October 2006, respectively). Other four tropical eruptions had very small aerosol perturbations and did not show any significant UTLS temperature change. Out of the two midlatitude eruptions, Sarychev peak had similar stratospheric aerosol perturbations as Soufrière Hills and Tavurvur eruptions, but did not show any significant UTLS temperature change. The volcanic signals in the UTLS temperature from the tropical Soufrière Hills and Tavurvur eruptions were observed for the period of 7 months after August 2006. A warming of 0.5–0.8 K in the tropical 16–18.5 km (100–70 hPa) layer was observed in association with these two tropical eruptions. Highlights: Effect from the eight recent (2001–2010) minor volcanic eruptions in the UTLS temperature was investigated. The tropical UTLS warming due to recent minor volcanic eruptions is analyzed using GPS RO, radiosonde and reanalysis datasets. A tropical UTLS warming of 0.5–0.8 K was observed in association with the Soufriere Hills and Tavurvur eruptions.